PENINGKATAN PEMAHAMAN MENGENAI DESAIN LABEL DAN KEMASAN PADA PRODUK OLEH-OLEH DI DESA WIDARAPAYUNG WETAN KABUPATEN CILACAP - Ayu Pramita; Oman Somantri; Oto Prasadi; Theresia Evila Purwanti Sri Rahayu; Nurlinda Ayu Triwuri; Ilma Fadlilah (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2022)
The number of Micro, Small and Medium Enterprises (MSMEs) in Indonesia as of September 2021 reached 64.2 million by contributing a GDP of around 61.07 percent and being able to absorb 97% of the total existing workforce, and was able to collect 60.42% of the total investment in Indonesia. This indicates that MSMEs have great potential to be developed, besides that MSMEs also contribute gross domestic product (GDP) in Indonesia, open opportunities to empower family finances, open business opportunities and absorb labor which in turn can improve the economy in Indonesia. However, the last two, the whole world has experienced economic paralysis caused by the Covid-19 pandemic outbreak, as well as what happened in Indonesia. One of them has experienced a bad impact on MSMEs/ MSEs. The product of various chips "Tunggal Makmur" is a household industry that still survives today even though with Covid-19, production has decreased by up to 50% during the Covid-19 pandemic. For the conditions mentioned above, the Cilacap State Polytechnic Lecturer intends to carry out Community Service (PKM) at the location of various chips in Widarapayung Wetan village, Cilacap Regency. Community service aims to provide information and knowledge coaching to increase understanding of the important role of business in packaging various chips to attract buyers. The method used in this activity is by surveying methods and directly involving spaciousness to conduct coaching and conducting questions and answers with participants. What is expected by guiding to increase understanding of information and knowledge and socialization is to be able to increase sales by providing attractive packaging and labels. The output will be produced in the form of videos and journals.